Ordenanza Pachamikuy: Un modelo participativo para sistemas alimentarios sostenibles - International Potato Center (2025)
In 2025, the Municipality of Pachacamac approved the Pachamikuy Ordinance, a pioneering initiative in Peru aimed at ensuring healthy diets and strengthening local agri-food systems. This video features the voices of key actors—authorities, civil society, producers, and international organizations—who explain how the ordinance promotes urban agriculture, food recovery, public procurement from farmers, the organization of farmers’ markets and community kitchens, and sustainable rural tourism.